A Case Study Evaluating the Fidelity of Suicide Prevention Workshops in California - Osilla, Karen Chan (RAND Corporation, 2014)
Reports on an evaluation of California suicide intervention training workshops to provide evidence that training is delivered with fidelity and adherence to the workshop's design, as well as with high quality.